PENGEMBANGAN HISTORICAL MODULE AND LAPBOOK (HIMLAP) PERJUANGAN KARAENG GALESONG UNTUK MENINGKATAN PEMAHAMAN SEJARAH LOKAL SISWA KELAS XI SMA NEGERI 1 NGANTANG - Rohana, Melda Amelia; Sayono, Joko; Utami, Indah Wahyu Puji (Jurnal Pendidikan Sejarah Indonesia, 2024)
Abstract:Ngantang, a region in Malang, East Java, is known for its local history detailing the struggle of Karaeng Galesong. Karaeng Galesong, a son of Sultan Hassanuddin from the Kingdom of Gowa in Makassar, actively fought against the Dutch East India Company (VOC) in East Java during the 17th century. After his prolonged struggle, Karaeng Galesong ultimately passed away and was laid to rest in Ngantang. Despite Karaeng Galesong's renown in Ngantang, numerous students in the area remain unfamiliar with the details of his struggle. This unfamiliarity stems from a dearth of references or educational materials pertaining to this particular aspect of local history. To address this issue, researchers developed the 'Historical Module and Lapbook' (HIMLAP) teaching materials, focusing on history of Karaeng Galesong's 17th-century struggle against the VOC in East Java. The objective is to deepen Ngantang students' understanding of their local history and assess HIMLAP's effectiveness as a teaching tool. HIMLAP, an innovative educational tool, merges a module with a lapbook, offering students an engaging and visually appealing learning experience. This research employs Sugiyono's Research and Development (R&D) methodology. However, this research and development phase did not progress to mass production. The validation tests conducted on the materials and teaching resources revealed that the HIMLAP teaching materials, focusing on history of Karaeng Galesong's 17th Century struggle against the VOC in East Java, are exceptionally suitable for pilot testing. In both small and large group trials, an increase in student understanding was observed, as evidenced by the improvement in scores from pretest to posttest. Given these positive outcomes, it can be concluded that the HIMLAP, detailing Karaeng Galesong's struggle, is highly feasible as a local history teaching resource in enhancing student understanding. Abstrak: Ngantang adalah salah satu wilayah di Malang, Jawa Timur yang memiliki sejarah lokal tentang perjuangan Karaeng Galesong. Karaeng Galesong merupakan salah satu anak dari Sultan Hassanuddin dari Kerajaan Gowa (Makassar) yang berjuang melawan VOC di Jawa Timur di abad ke-17. Di akhir perjuangannya, Karaeng Galesong akhirnya meninggal dan dimakamkan di Ngantang. Meskipun tokoh Karaaeng Galesong terkenal di Ngantang, namun banyak siswa di Ngantang yang tidak memahami sejarah perjuangan Karaeng Galesong. Hal tersebut dikarenakan tidak adanya referensi atau bahan ajar mengenai materi sejarah lokal tersebut. Untuk mengatasi permasalahan tersebut, peneliti mengembangkan bahan ajar Historical Modul and Lapbook (HIMLAP) sejarah perjuangan Karaeng Galesong melawan VOC di Jawa Timur abad ke-17. Penelitian ini bertujuan untuk meningkatkan pemahaman siswa di Ngantang mengenai sejarah lokalnya dan menguji efektivitas bahan ajar HIMLAP ini sebagai bahan ajar sejarah lokal. HIMLAP ini merupakan bahan ajar inovatif yang menggabungkan modul dengan lapbook agar memberikan tampilan yang menarik bagi siswa. Metode yang digunakan dalam penelitian ini adalah metode Research and Development (R&D) Sugiyono, namun peneliti dalam penelitian dan pengembangan ini tidak sampai pada tahap produksi masal. Dari hasil uji validasi materi dan bahan ajar oleh validator, didapatkan hasil bahwa bahan ajar HIMLAP Sejarah Perjuangan Karaeng Galesong Melawan VOC di Jawa Timur Abad ke-17 ini sangat layak untuk di ujicobakan. Dalam ujicoba kelompok kecil maupun ujicoba kelompok besar didapatkan hasil adanya peningkatan pemahaman siswa yang ditunjukkan dengan adanya peningkatan hasil pretest ke posttest. Dengan adanya hasil tersebut, dapat disimpulkan bahwa HIMLAP perjuangan Karaeng Galesong ini sangat layak untuk menjadi bahan ajar sejarah lokal dalam meningkatkan pemahaman siswa.